THE IMPACT OF DIGITAL TRANSFORMATION ON ORGANIZATIONAL AGILITY: A COMPARATIVE STUDY OF EMERGING MARKET - Farikhul Muafiq (Penelitian dan Pengembangan Ilmu, 2024)
Digital transformation (TD) is the key to increasing organizational agility (OA) in a competitive era, but emerging markets face unique challenges due to limited resources. This research aims to identify key barriers to achieving OA through TD in resource-limited emerging markets, and offers literature-based recommendations for overcoming them. By using the method Systematic Literature Review (SLR) based on the PRISMA framework, this research analyzes 28 articles relevant data from Scopus databases, Web of Science, and others. Results show that key barriers include limited digital infrastructure, lack of managerial skills, and cultural resistance to change, while proposed solutions involve cross-sector collaboration, increased digital capacity, and government policies that support innovation ecosystems. The implications of this research provide strategic insights for policymakers, organizational leaders, and practitioners to drive effective TD in emerging markets.